Advances in spermatogonial stem cell research: A systematic review and bibliometric analysis (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Spermatogonial stem cells (SSCs) are an exceptionally rare group of testicular cells that give rise to all subsequent male germ cells, the basis of spermatogenesis and male fertility. The SSCs have shown great potential in livestock breeding systems, medical applications, and genetic conservation of endangered species. In this study, we used bibliometric analysis to assess worldwide research trends in the SSCs area based on publication outputs, co-authorships among authors, and affiliated countries. A systematic review was performed to discuss: 1) current drawbacks in developing the SSCs culture system, 2) current progress in SSC transplantation in various species, and 3) potential applications of the male germline stem cells. Results of the bibliometric analysis on the Scopus database showed a total of 2171 research articles issued between 1965 to 2023. With a consistent annual publication of more than 100 articles, it was suggested that a strong interest in SSC research started in the last 11 years. About 54% of the total global publications were contributed by researchers from the United States of America (USA) and China, leading the other 59 countries/territories. The studies highlighting and discussing SSCs from the present future and prospects are useful to researchers, academicians, and policymakers.
Keywords: bibliometric analysis; male fertility; spermatogonial stem cell; systematic review; transplantation